Microwave activation of electrochemical processes at microelectrodes - Compton, R; Coles, B; Marken, F (1998)
Electrochemical experiments at platinum microdisc electrodes are shown to be possible in an environment of intense microwave radiation and a considerable current enhancement observed for the ferrocyanide/ferricyanide redox couple in aqueous 1 M KCl is shown to be Faradaic in nature consistent with a rapid heating effect causing the temperature in the liquid phase at the electrode/solution interface to locally superheat.